UWB in Medicine – High Performance UWB Systems for Biomedical Diagnostics and Short Range Communications - Lin, Dayang; Mirbach, Michael; Thiasiriphet, Thanawat; Lindner, Jürgen; Menzel, Wolfgang; Schumacher, Hermann; Leib, Mario; Schleicher, Bernd (IntechOpen, 2013)
None